Evaluation of Direct Terahertz Radiation on Prospective Communication Applications - Catur Apriono; Dzakwan Widyo Pangestu (International Journal of Electrical, Computer, and Biomedical Engineering, 2023)
The continuous development of information and communication technology has brought rapid changes, especially developments in cellular technology, starting with 1G and reaching the fifth development in 2020, 5G. This development continues, as evidenced by the start of 6G technology development in early 2020. The Terahertz (THz) spectrum, which has not been used optimally so far for communication technologies, is one candidate to support the next cellular technology developments. THz Waves offers far wider bandwidth than the existing technologies. Apart from the advantages of THz wave radiation, this research studies THz wave radiation intensity and its potential for communication. By calculating the Atmospheric Attenuation, FSPL and considering the minimum received power of user equipment (UE), THz wave radiation characteristics will be more optimal for use less than 500 meters at 0.1 THz and less than 100 meters at 3 THz. The highest Power density of THz radiation is 7.99 × 10-11 Watt/m2 when using 0.1 THz as frequency and a power transmitter of 10 Watts. The results show that exposure to THz waves in communication applications is safe and acceptable for practical communication use.